Phytochemical study of the alkaloid from the bulbs of Eucharis grandiflora Planchon (Fam. Amaryllidaceae) - Sarmiento, Ma. Teresita R.
The fresh bulb of Eucharis grandiflora Planchon of the Family Amaryllidaceae contains a greater amount of alkaloid than a dried sample. So far, there is no study and chemical investigation yet made on the alkaloid content of the bulb of this plant.